Teachers writers celebrities ; Intellectuals of modernFrance - Debray, Regis; Macey, David(Tr.) (London, 1981)
It is difficult to speak of 'the intellectuals' as a distinct social category without thinking of France. In no other country, as Régis Debrayob serves, are intellectuals as such so widely almost ritually deferred to. Yet their public eminence contrasts strangely with the absence of any systematic analysis of their actual social role. Debray makes good this absence by examining the historical and social constitution of the intelligentsia in relation to the main centers of cultural power in modern France. The fulcrum of his book is an incisive account of the 'three ages' of the intellectuals, commanded by the university, then publishing, and now the media. Then follows a witty anatomical dissection of the professional and social mores of the intellectuals in their latest, 'mediatic' incarnation - as star performers in the press and on TV. Debray denounces the intellectual-as-celebrity, seeing in this new social type an abdication from the traditional functions of the intelligentsia and a strengthening of the reigning political order. Against it he invokes the critical spirit of an earlier generation and the Programme of a new science: mediology.
Keywords: Interllectuals France History .